FINANCIAL AND NON-FINANCIAL ANALYSIS OF TOYOTA AND FORD: A COMPARATIVE STUDY - Wang Xiaohui; Ooi Kok Loang; Duan Xinyao; Xu Wen; Xu Jingjing (Journal of Islamic, Social, Economics and Development, 2023)
This study performs a comparative financial and non-financial analysis of two major automobile companies, Toyota and Ford. The aim of this research is to provide potential investors with insights on the financial performance of these companies and make a recommendation on which company would be a better investment option. To achieve this, a comprehensive analysis of the two companies is conducted using Porter's Five Forces framework to analyze the industry, trend analysis and percentage change analysis to evaluate financial performance, interpretation of ten financial ratios, and common size statement analysis. The study finds that both companies face stiff competition, but Toyota has a stronger market position due to its strong brand image and diversified product portfolio. The financial analysis reveals that Toyota has better financial performance than Ford, with higher profitability, liquidity, and efficiency ratios. In terms of non-financial factors, Toyota has a better reputation for quality and sustainability initiatives. Based on the financial and non-financial analysis, the study recommends that Toyota would be a better investment option for potential investors. Overall, this study provides a valuable resource for investors looking to make informed decisions on investing in the automobile industry.